Cytochrome P450arom, androgen and estrogen receptors in pig sperm - Panza Rocco; Carpino Amalia; Aquila Saveria; Rago Vittoria (BMC, 2007)
Abstract Background Androgens and estrogens are crucial for mammalian sperm differentiation but their role in biology of mature male gamete is not still defined. The expression of proteins involved in the biosynthesis and action of these steroid hormones has been demonstrated in human spermatozoa, but very few data have been reported in mature sperm from non human species. The purpose of the current study was to investigate the expression of aromatase (P450arom), estrogen (ERalpha/ERbeta) and androgen (AR) receptors in ejaculated spermatozoa of pig. Methods The immunfluorescence experiments were carried out treating pig sperm with anti-P450arom, anti-ERalpha, anti-ERbeta and anti-AR as primary antibodies, while Texas-Red/FITC conjugated IgG were applied as secondary antibodies. Furthermore, Western blot analysis was performed on sperm lysates. Results Aromatase was immunolocalized in the sperm tail, ERalpha and AR were localised in the sperm midpiece, while ERbeta was confined in the acrosomal region of the male gamete. Immunoblots detected a ~52 kDa aromatase band, a ~110 kDa AR band, a ~67 kDa ERalpha and two ERbeta bands, at ~50 kDa and ~59 kDa. Conclusion This is the first report demonstrating that pig ejaculated spermatozoa express aromatase, estrogen and androgen receptors with a differential intra-cellular localization revealing a specie-specific expression pattern. Therefore, pig sperm could be considered as a potential estrogen source while the different hormone cellular sites suggest distinct roles of androgens and estrogens in pig sperm physiology.